2017
DOI: 10.1080/13674676.2017.1414170
|View full text |Cite
|
Sign up to set email alerts
|

Sexual abuse and HIV-risk behaviour among black and minority ethnic men who have sex with men in the UK

Abstract: Black and minority ethnic (BME) men who have sex with men (MSM) face a major burden in relation to HIV infection. It was hypothesised that sexual abuse would predict sexual risk-taking, and that this relationship would be mediated by victimisation and maladaptive coping variables. Four hundred and thirty-two BME MSM completed the survey; 54% reported no sexual abuse and 27% reported sexual abuse. Mann-Whitney tests showed that MSM with a history of sexual abuse reported higher frequency of drug use, and of hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…BAME MSM are 6% more likely to present for CDU than white MSM, though the literature reports that CDU is associated more with white than BAME MSM 12. It may be the case that though proportionally fewer BAME MSM engage in CDU, they are over-represented in MSM with problematic drug use due to increased societal and psychosocial stressors relative to white MSM 17–19. Without reliable prevalence estimates for CDU in the UK, this small difference is difficult to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…BAME MSM are 6% more likely to present for CDU than white MSM, though the literature reports that CDU is associated more with white than BAME MSM 12. It may be the case that though proportionally fewer BAME MSM engage in CDU, they are over-represented in MSM with problematic drug use due to increased societal and psychosocial stressors relative to white MSM 17–19. Without reliable prevalence estimates for CDU in the UK, this small difference is difficult to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…It would be informative to compare situational stressors, psychological self-schemata, coping strategies and mental health outcomes between specific ethnic minority groups, such as Pakistanis and Indians, who exhibit distinct levels of social capital. Third, previous research has revealed a high prevalence of childhood sexual abuse in BAME gay and bisexual men in the UK (Jaspal et al, 2017). As a situational stressor with enduring negative psychosocial consequences, childhood sexual abuse should be measured as a potential predictor of negative psychological self-schemata in future research into depressive symptomatology in BAME LGB people in the UK.…”
Section: Limitationsmentioning
confidence: 97%
“…Furthermore, perceived exclusion from multiple social groups can lead to feelings of marginalization, leaving individuals with decreased self-esteem, internalized homophobia, and few sources of social support (Jaspal & Cinnirella, 2010). In a study of 432 South Asian gay and bisexual men (Jaspal et al, 2017), it was found that the experience of childhood abuse was related to higher frequency of substance misusepossibly as a maladaptive coping strategy. It is not known, however, whether these challenges to psychological wellbeing can lead to depressive symptomatology in BAME LGB people in the UK.…”
Section: Identity and Mental Health In Bame Lgb Peoplementioning
confidence: 99%
“…The psychological stressors associated with being of sexual and ethnic minority backgrounds may increase the risk of poor mental health. BAME LGB people experience internalised homophobia (Barnes & Meyer, 2012), heterosexism (Sung, Szymanski, & Henrichs-Beck, 2015) hypervigilance (Jaspal et al, 2017) and a lack of social support (Jaspal, 2014) and engage in maladaptive behaviours (Ayala et al, 2012). Yet, the question of whether the effects of multiple stigmatised identities are additive or synergistic (Cochran, 2001) has not yet been addressed in the UK context.…”
Section: The Mental Health Of Bame Lgb People In the Ukmentioning
confidence: 99%